The need for social support for patients suffering from brain tumour - Jolanta Celej-Szuster; Magda Polit; Elżbieta Przychodzka; Katarzyna Piasecka; Krzysztof Turowski; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Introduction. Central nervous system tumours establish a group of benign and malignant tumours stemming from various nervous system cells [1]. In every stage of cancer the patient needs help and support compensating the deficits in psychophysical health. The term "social support" is used interchangeably with the following expressions: help, relationships, bonds, social relationships, connections [5,6]. Objective. The aim of the study was to assess the need for social support for patients suffering from brain tumour. Results. For patients suffering from brain tumour the most needed form of support is emotional. Conclusions. There is a relationship between certain sociodemographic data (marital status, family type) and the need for a certain kind of social support (personal or professional/formal support).